4 - Ensuring Peace and Reconciliation while Holding Leaders Accountable: The Politics of ICC Cases in Kenya and Sudan - Murithi, Tim (Africa Development, 2021)
The International Criminal Court (ICC) was established as a permanent independent institution to prosecute individuals who have committed or are implicated in the most serious crimes of international concern including genocide, crimes against humanity and war crimes. This study assesses the challenge of ensuring peace and reconciliation while holding leaders accountable, with specific reference to the politics of the ICC cases in Sudan (Darfur) and Kenya. In particular, this article argues that the issue of prosecuting alleged perpetrators is problematic with respect to the cases that the ICC is currently engaged in. The study argues that since the ICC has become involved in peace, reconciliation and political processes, it thus has the potential to disrupt such initiatives if its interventions are not appropriately sequenced. The study further argues that both President Omar al-Bashir of Sudan, and subsequently President Uhuru Kenyatta of Kenya, managed to politicize the ICC interventions in their countries. The article concludes that this process of politicization of the Court’s interventions in Sudan and Kenya, eventually led the ICC into a political stand- off with the African Union (AU), with the United Nations Security Council being an unresponsive but implicated secondary actor. The study also concludes that since neither the ICC nor the AU have managed to find a way out of the impasse, there is a need to develop some innovative strategies. This article therefore offers some insights into a prospective way forward.